Small intestinal bacterial overgrowth in patients with rheumatoid arthritis. Issue 7 (July 1993) - Henriksson, A E; Blomquist, L; Nord, C E; Midtvedt, T; Uribe, A
Abstract : OBJECTIVES--To examine the microflora of the upper small intestine in patients with seropositive rheumatoid arthritis (RA) using a combination of microbial cultivation and tests for microbial metabolic activity. METHODS--Twenty five patients with seropositive RA, 12 achlorhydric control subjects, and 11 control subjects with normal gastric acid secretion were investigated. Disease activity was evaluated in the patients with RA by three different indices. Eight (32%) of the patients with RA had hypochlorhydria or achlorhydria. The acid secretory capacity was determined with pentagastrin stimulation. A modified Crosby capsule was used to obtain biopsy specimens and samples of intestinal fluid from the proximal jejunum; aerobic and anaerobic microbial cultivation of mucosal specimens/intestinal fluid was carried out, and gas production and microflora associated characteristics in jejunal fluid were determined. Additionally, a bile acid deconjugation breath test was performed. RESULTS--Subjects with at least one of the following findings were considered to have bacterial overgrowth: positive bile acid deconjugation test; growth of Enterobacteriaceae; positive gas production; or low tryptic activity. By these criteria half of the patients with RA with hypochlorhydria or achlorhydria and half of the achlorhydric controls had bacterial overgrowth. Thirty five per cent of the patients with RA with normal gastric acid secretion had bacterial overgrowth compared with none of the normal controls. Disease activity indices and rheumatoid factor titres were significantly higher in patients with RA with bacterial overgrowth than in those without. CONCLUSIONS--A high frequency of small intestinal bacterial overgrowth was found in patients with RA; it was associated with a high disease activity and observed in patients with hypochlorhydria or achlorhydria and in those with normal acid secretion.